ANALYSIS OF THE RELATIONSHIP BETWEEN KNOWLEDGE LEVELS AND STUDENTS ATTITUDES TOWARDS THE SELECTION OF HEALTH SUPPLEMENTS IN FACING COVID 19 IN THE PANDEMIC ERA - Heny Puspasari; Weni Puspita; Sinta Sinta (Jurnal Ilmiah Farmako Bahari, 2022)
Background: Coronavirus Disease 2019 (Covid 19) has happened declared by WHO a global pandemic. Covid 19 in Indonesia has displayed a type of disease that causes public health emergencies and non-natural disasters, which cause death and considerable economic losses. Objective: This study determined the relationship between student knowledge and attitudes towards selecting health supplements in dealing with Covid 19. Methods: The research has been carried out using a descriptive survey method with a prospective approach. Sampling has been done using a stratified random sampling technique for active students at the Akademi Farmasi Yarsi Pontianak at all levels/semesters. In addition, this research has conducted by giving a questionnaire via a google form. Results: The study obtained was processed with the chi-square analysis test. Results show from the chi-square analysis that there is a relationship between the level of knowledge and attitudes of students towards the selection of health supplements in dealing with Covid 19 in the pandemic era with a value (p-value (0.000) < alpha (0.05). Conclusion: The analysis results show a relationship between the level of knowledge and student attitudes towards selecting health supplements in the face of Covid 19 in the pandemic era.